2005
DOI: 10.2166/wst.2005.0485
|View full text |Cite
|
Sign up to set email alerts
|

Sewage outfall plume dispersion observations with an Autonomous Underwater Vehicle

Abstract: This work represents one of the first successful applications of Autonomous Underwater Vehicles (AUVs) for interdisciplinary coastal research. A monitoring mission to study the shape and estimate the initial dilution of the S. Jacinto sewage outfall plume using an AUV was performed on July 2002. An efficient sampling strategy enabling greater improvements in spatial and temporal range of detection demonstrated that the sewage effluent plume can be clearly traced using naturally occurring tracers in the wastewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…high CDOM) typically having low salinity. It is evident that the core of the plume (highest CDOM values) consists of elevated CDOM levels of approximately 1.3 ppb over the surroimding waters which equate to a minimum dilution of approximately 1:141, Previous work used salinity signatures and inifial mixing lines to estimate dilufion near the diffuser (Washburn et al 1992;Ramos et al 2005). The salinity differences between plume waters and background waters for the 3 March 2011 monitoring mission are approximately 0.05 psu (Figure 4).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…high CDOM) typically having low salinity. It is evident that the core of the plume (highest CDOM values) consists of elevated CDOM levels of approximately 1.3 ppb over the surroimding waters which equate to a minimum dilution of approximately 1:141, Previous work used salinity signatures and inifial mixing lines to estimate dilufion near the diffuser (Washburn et al 1992;Ramos et al 2005). The salinity differences between plume waters and background waters for the 3 March 2011 monitoring mission are approximately 0.05 psu (Figure 4).…”
Section: Resultsmentioning
confidence: 97%
“…A challenge in accurately tracking a wastewater plume is the design of an effective sampling plan which adapts to variable océanographie conditions in the environment (Ramos et al 2002). For the 3 March 2011 PLOO mission, the most probable missions were planned prior to sampling based on near real-time océanographie conditions at the outfall as monitored by the buoy coupled with plume model predictions.…”
Section: Mission Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of mission plan changes might be for a vehicle to search for and then modify its trajectory to follow a characteristic, such as an outfall plume or a thermocline [4]; it might be for a vehicle to have to modify its path to avoid an obstacle, or to search for, find and follow a feature, such as a buried pipeline; or it might be for an action to be taken by a vehicle when a particular value is registered on a sensor, such as the collection of a water sample if the concentration of a particular chemical reaches a certain value, or for fault tolerance [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…The recent use of AUVs in a wide range of applications has shown their potential as a mobile sensor in ocean outfall mapping. For ocean outfall monitoring and plume tracking applications, several studies [6] [7] [8] using the REMUS class AUV and one study [9] using the ARCS class AUV have been reported. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%